FUNDAMENTALS OF OIL SPILL CLEAN-UP TECHNOLOGY USING NATURAL CLINOPTYLOLITE - Гринишин, Станіслав; Знак, Зеновій (SWorldJournal, 2025)
The paper examines the ability of natural clinoptilolite to sorb oil in the event of its spill on solid surfaces. It is shown that oil sorption begins, in most cases, immediately after contact with clinoptilolite particles. The regularities of oil sorpti